Some Properties of Sp-Closed Spaces and Sp-Closed Relative to Spaces - Shareef, H A. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The purpose of this paper is to introduce two types of sets called Sp- #- open and Sp-regular set in topological spaces and study more properties of Sp-closed spaces, Sp-closed relative to spaces interms of these two sets.